Plumage polymorphism in a newly colonized black sparrowhawk population: classification, temporal stability and inheritance patterns. (18th September 2012) - Amar, A.; Koeslag, A.; Curtis, O.; Kitchener, Andrew
Abstract Persistent plumage polymorphism occurs in around 3.5% of bird species, although its occurrence is not distributed equally across bird families or genera. Raptors show a disproportionately high frequency of polymorphism, and among raptors it is particularly frequent among the Accipiter hawks. However, no systematic study of polymorphism in this genus exists. Using a long‐term study of the black sparrowhawk (Accipiter melanoleucus), a widespread polymorphic African Accipiter, we first demonstrate that the species shows discrete polymorphism (cf. continuous polymorphism), occurring as either dark or light morph adults, and that morph type and plumage pattern are invariant with age. We then demonstrate that adult morph type follows a typical Mendelian inheritance pattern, suggesting a one‐locus, two‐allele system within which the allele coding for the light morph is dominant. This inheritance pattern provides further support for classifying polymorphism in this species as discrete. In most of the species' range the dark morph is the rarer morph; however, in our study population where the species is a recent colonist, over 75% of birds were dark and this remained fairly constant over the 10 years of our study. This reversal in morph ratio may represent an adaptive response to different environmental conditions or could be a founder effect with colonizing individuals having been mostly dark morph birds simply by chance. The extreme differences in environment conditions (seasonality of rainfall) that occur across the species' range in South Africa provide support for an adaptive explanation, but further work is needed to test this hypothesis.